Kinerja Dinas Pertanian Tanaman Pangan dalam Program Penyaluran Pupuk Bersubsidi Tahun 2018 -2023: (Studi Kasus Petani Padi di Desa Seso Kabupaten Ngada) - Mauritsia Mayasandri Keo; Laurensius P. Sayrani; Theny I.B.K Pah; Made N.D Andayana (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to determine and evaluate the Performance of the Food Crops Agriculture Service in the 2018-2023 Subsidized Fertilizer Distribution Program (Case Study of Rice Farmers, in Seso Village, Ngada Regency). Using a qualitative descriptive approach with Atik Septi Winarsih's theory and Robbins' theory which highlights Responsiveness, Responsibility, Accountability, Punctuality, Work Commitment. The study involved 12 Informants.The results showed that in the subsidized fertilizer distribution program, employees of the Food Crop Agriculture Office of Ngada Regency have not carried out their duties in accordance with the needs of farmers on agricultural land, this is due to communication deficiencies such as in terms of providing infrastructure, fertilizer stocks, and the problem of changing fertilizer price increases and in terms of special training in accessing the E-RDKK system. One of the factors that hinders access to this system is that farmers do not understand the use of the E-RDKK system through android phones and the lack of knowledge that farmers have. The Ngada Regency Food Crop Agriculture Office has also not provided sufficient facilities and infrastructure on farms because there are many delays in distribution that take more time than the specified time. Services at the Ngada Regency Food Crop Agriculture Office have not been in accordance with the implementation in the field so that farmers' needs have experienced delays in service. Another form of participation that supports the sustainability of the subsidized fertilizer distribution program is by conducting socialization activities. The form of participation that is carried out is contrary to community expectations where the completion time is delayed from the time that should be determined.